THE SYMBOLS OF DEMOCRACYA SEMIOTICS ANALYSIS TO "THE SAX"A NOVEL BY SUJIWO TEJO - Achdi Merdianto, - (2009)
This study is an analysis to the novel entitled The Sax (The Saxophone) employing semiotics theory, notably the triadic model as its analysis tool. The research is aimed at revealing the answers to the four formulated research questions: (1) what are the symbols of democracy used by the author in the text? (2) how does the novel represent democracy? (3) how do the characters make meanings of democracy? and (4) what form of democracy is represented in the novel? To answer the four formulated research questions above, the study is divided into two steps: first, that all of the expressions in the novel the Sax which represent the symbols of democracy are taken as the data of the study. The data are in the form of words, phrases, or sentences, and second by means of Pierce's triadic model, the data are then analyzed to find out the characteristics and the representations of democracy in the novel the Sax by studying the Representamen, Object, and Interpretant. The result of the study shows that the symbols of democracy can be seen in the way the characters express the term democracy and relate democracy to their environment around them whether it is metaphorically described on the pioneers or figures of democracy itself. Furthermore, the democracy symbolizes the existence and the demands of freedom and equality, the representatives parliamentary, the election, and also pluralism. From all of the previous characteristics of democracy, the study shows that the occurrences to the demands of freedom and equality are the highest in frequency compared to the other elements of democracy. This concludes that the form of democracy represented in the novel is the Liberal Democracy.